A 75.7GHz to 102GHz rotary-traveling-wave VCO by tunable composite right /left hand T-line - Ma, Shunli (2013)
With the use of tunable composite-right/left-hand (CRLH) transmission line (T-line), this paper provides a wide frequency-tuning-range (FTR) mechanism for Mobius-ring rotary-traveling-wave (RTW) VCO in millimeter-wave region. CRLH T-line is implemented in RTW-VCO with inductor-loaded transformer to realize sub-band selection over a wide FTR. Each sub-band is further covered by a varactor for fine-tuning. The chip was fabricated in GF 65nm RF-CMOS process with area of 0.08mm2. The measured results show a current consumption of 14mA under supply voltage of 1V, a tuning range of 29.5% with center frequency at 89.3GHz, and a phase noise from -100.08dBc/Hz to -98.7dBc/Hz with 10MHz offset. A state-of-art figure-of-merit FOMT of -177.78dBc/Hz is demonstrated.